Erratum to: Cervical Schwannoma of Sympathetic Chain: A Rare Case Report - Bin Zulkifli, Muhd Faiz; Kenali, Solahudin Mohd (Central Asian Journal of Medical Sciences, 2018)
In the report entitled “Cervical Schwannoma of Sympathetic Chain: A Rare Case Report” (2018; 4: 92-95), by Bin Zulkifli and Kenali, DOI: 10.24079/cajms.2018.03.012 the reference list at the end of the article was incomplete. The complete list of references is found below.